Evaluation of the Green Campus Program at the University of A Coruña - Martina Dono; Verónica Torrijos; Manuel Soto (Universitas Diponegoro, 2023)
Green Campus (GC) is an international program launched by the Foundation for Environmental Education (FEE) which includes the philosophy, methodology and experience of Eco-schools, adapted to the specific university needs and problems. Through its seven-steps methodology, the GC program can be considered a kind of environmental management system, which includes external evaluation and pursues continuously improved environmental performance. The GC program began at the UDC in 2014, with autonomous implementation at the center level, promoting bottom-up initiatives in combination with other top-down initiatives. In 2022 it had reached all 20 UDC teaching centers, more than half of them having already achieved program certification (green flag award). This paper analyses the evolution and performance of the GC program at UDC, through two on-line surveys addressed to 1) students in general, and 2) coordinators and members of the environmental committees. Some difficulties identified are low involvement and participation of students and overload of tasks of all kinds, which hinders the volunteer participation of committee members. Nevertheless, a good overall rating was given to the program from participating staff and students. A SWOT analysis is also presented, summarizing the information obtained through surveys, together with the Office for the Environment's experience in the coordination of the different centers involved in the program. Finally, a strategy is proposed to improve the visibility of the GC among students and enhance their participation.